Molecular and Cellular Response of the Myocardium (H9C2 Cells) Towards Hypoxia and HIF-1α Inhibition - Osuru, Hari Prasad; Lavallee, Matthew; Thiele, Robert H. (Frontiers in Cardiovascular Medicine, 2022)
INTRODUCTION: Oxidative phosphorylation is an essential feature of Animalian life. Multiple adaptations have developed to protect against hypoxia, including hypoxia-inducible-factors (HIFs). The major role of HIFs may be in protecting against oxidative stress, not the preservation of high energy phosphates. The precise mechanism(s) of HIF protection is not completely understood. METHODS: In order to better understand the role of hypoxia-inducible-factor 1, we exposed heart/myocardium cells (H9c2) to both normoxia and hypoxia, as well as cobalt chloride (prolyl hydroxylase inhibitor), echniomycin (HIF inhibitor), A2P (anti-oxidant), and small interfering RNA to beclin-1. We measured cell viability, intracellular calcium and adenosine triphosphate, NADP/NADPH ratios, total intracellular reactive oxidative species levels, and markers of oxidative stress. RESULTS: hypoxia (1%) lead to increased intracellular Ca2+ levels, and this response was inhibited by A2P and echinomycin (ECM). Exposure of H9c2 cells to hypoxia also led to an increase in both mRNA and protein expression for Cav 1.2 and Cav 1.3. Exposure of H9c2 cells to hypoxia led to a decrease in intracellular ATP levels and a sharp reduction in total ROS levels. The impact of hypoxia on ROS was reversed with HIF-1 inhibition through ECM. Exposure of H9c2 cells to hypoxia led to an increase in both ATG5 mRNA and protein expression, as well as a decrease in mitochondrial mRNA. Both A2P and ECM attenuated this response to varying degrees. CONCLUSIONS: Hypoxia leads to increased intracellular Ca2+, and inhibition of HIF-1 attenuates the increase in intracellular Ca2+ that occurs with hypoxia. HIF-1 expression leads to decreased adenosine triphosphate levels, but the role of HIF-1 on production of reactive oxidative species remains uncertain. Anti-oxidants decrease HIF-1 expression in the setting of hypoxia and attenuate the increase in Ca2+ that occurs during hypoxia (with no effect during normoxia). Beclin-1 appears to drive autophagy in the setting of hypoxia (through ATG5) but not in normoxia. Additionally, Beclin-1 is a powerful driver of reactive oxidative species production and plays a role in ATP production. HIF-1 inhibition does not affect autophagy in the setting of hypoxia, suggesting that there are other drivers of autophagy that impact beclin-1.